PENGEMBANGAN OBJEK WISATA NAGARI TUO PARIANGAN OLEH DINAS PARIWISATA PEMUDA DAN OLAHRAGA KABUPATEN TANAH DATAR - Wanda Gustri Yomi; M. Fachri Adnan; Zikri Alhadi (JPSI (Journal of Public Sector Innovations), 2019)
This research is motivated by the still existing problems in Nagari Tuo Pariangan tourism objects in the form of development that has not been maximized. This study aims to find out and describe (1) the development of Nagari Tuo Pariangan tourism objects by the Youth and Sports Tourism Office of Tanah Datar Regency; (2) Factors that become obstacles and supporters in the development of Nagari Tuo Pariangan tourism objects. This type of research is qualitative research with descriptive methods. The informants in this study were determined by purposive sampling technique. The data of this study are  primary and secondary data. These data are collected by conducting interviews, observation, and documentation studies. Techniques for testing the validity of data by source triangulation. While the data analysis techniques used are data collection, data reduction, data presentation and verification of conclusions. The results showed that the development carried out by the Tourism Office was limited to maintaining and repairing damaged tourism objects, providing assistance in the form of strawberry seeds and promoting tourism. Tourist attractions held are Pacu Jawi. The broken and damaged road has been repaired and some facilities and infrastructure have been added such as toilets and Mushallah. The souvenir center and souvenirs were just finished. HR development in the form of pokdarwis formation. The Tourism Office also empowers two residents as tour guides. The supporting factors in this development: 1) One of the most beautiful villages in the World. 2) Tourism infrastructure is very adequate. 3) The gift center has just been completed and there is a reading corner. 4) Damaged and hollow roads have been repaired 5) There is a tour group called Pokdarwis and Tourguide. Inhibiting factors in this regard: 1) Brousur about partially abandoned tourist objects and some damaged tourist objects that have not been repaired as well as tourist attraction is only pacu jawi. 2) Parking space is still inadequate. 3). Not yet complete gift shop.4) Pokdarwis is still not maximal in managing tourist attractions. 5) The cleanliness of tourist objects is still lacking and the janitor is only two people.